Virtual Reality for Training: Evaluating Retention of Procedural Knowledge - Hall, Craig R.; Horwitz, Carol D. (International Journal of Virtual Reality, 2001)
We conducted a study that contrasted the effects of virtual reality versus conventional computerbased instruction on retention of a simple procedure involving equipment operation. Seventy-two subjects between the ages of 20 and 30 were recruited from the general public. An intelligent tutor was used to manage the instruction in both treatments. The results were consistent with earlier research that reports that VR may not be superior to conventional electronic media for training certain intellectual skills. Implications for future research are discussed.